Lecturers’ and Students’ Responses toward the Implementation of the Merdeka Belajar-Kampus Merdeka (MBKM) Program at Alma Ata University - Ahmad Salim; Tri Rochmadi; Yulinda Kurniasari; Rusny Istiqomah Sujono; Rosa Nikmatul Fajri; Nurul Kusumawardani; Andi Wahyudi; Muh. Mustakim (AL-ISHLAH: Jurnal Pendidikan, 2022)
Independent Learning-Independent Campus (MB-KM) is a policy that has been issued by the government and is contained in the Regulation of the Minister of Education and Culture Number 3 of 2020 related to the National Standards for Higher Education. Students don't only have one skill, but also several skills through the MBKM program. In addition, lecturers are required not only to teach related content but also to improve soft skills and implementation so that students can achieve the expected graduate achievement targets and be ready to work. The purpose of this study was to determine the response of students, lecturers and education staff to the MBKM program, and the implementation of the Tridharma at Alma Ata University. This type of research is qualitative cross-sectional study and data collection using a questionnaire survey online method.  The sample of this study was students and lecturers at Alma Ata University, until the completion of the study, the sample size was 855 students and 114 lecturers. The survey was conducted online through the MBKM implementation questionnaire with the type of closed-ended question. The results of this study indicate that students are excited to participate in MBKM activities, particularly within the framework of the internship program and the real work lecture (KKN). In addition, it is known that there is still a low understanding of students, several lecturers, educational staff, and partners regarding policies and Standard Operating Procedures (SOP) for MBKM activities made by both the University and the Study Program level. The socialization associated with this program must be ongoing with the university community and educational partners. The response and implementation of MBKM that has been carried out well will be able to produce graduates with hard skills and soft skills who are ready to face the world of work independently, innovatively, and tough.